Establishment of mouse embryonic stem cells from isolated blastomeres and whole embryos using three derivation methods - González, Sheyla (Springer US, 2010)
PURPOSE: The aim of the present study is to compare three previously described mouse embryonic stem cell derivation methods to evaluate the influence of culture conditions, number of isolated blastomeres and embryonic stage in the derivation process. METHODS: Three embryonic stem cell derivation methods: standard, pre-adhesion and defined culture medium method, were compared in the derivation from isolated blastomeres and whole embryos at 4- and 8-cell stages. RESULTS: A total of 200 embryonic stem cell lines were obtained with an efficiency ranging from 1.9% to 72%. CONCLUSIONS: Using either isolated blastomeres or whole embryos, the highest rates of mouse embryonic stem cell establishment were achieved with the defined culture medium method and efficiencies increased as development progressed. Using isolated blastomeres, efficiencies increased in parallel to the proportion of the embryo volume used to start the derivation process.